2009
DOI: 10.1289/ehp.0800134
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum Testosterone Associated with Elevated Polychlorinated Biphenyl Concentrations in Native American Men

Abstract: BackgroundPolychlorinated biphenyls (PCBs) and chlorinated pesticides are endocrine disruptors, altering both thyroid and estrogen hormonal systems. Less is known of action on androgenic systems.ObjectiveWe studied the relationship between serum concentrations of testosterone in relation to levels of PCBs and three chlorinated pesticides in an adult Native American (Mohawk) population.MethodsWe collected fasting serum samples from 703 adult Mohawks (257 men and 436 women) and analyzed samples for 101 PCB conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
50
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 58 publications
6
50
1
2
Order By: Relevance
“…The inhibin-B concentration decreased significantly in men classified as obese compared with those with normal BMIs, confirming results by Globerman et al (23), who studied men with severe obesity (BMI > 40 kg/m 2 ), and Winters et al (24), who reported on 72 healthy men aged 18-24 years. The serum concentration of total T was significantly lower in obese men compared with men with normal BMIs, consistent with previous results (8,25). However, in linear or multiple regressions, BMIs were not correlated with T or FSH.…”
supporting
confidence: 91%
“…The inhibin-B concentration decreased significantly in men classified as obese compared with those with normal BMIs, confirming results by Globerman et al (23), who studied men with severe obesity (BMI > 40 kg/m 2 ), and Winters et al (24), who reported on 72 healthy men aged 18-24 years. The serum concentration of total T was significantly lower in obese men compared with men with normal BMIs, consistent with previous results (8,25). However, in linear or multiple regressions, BMIs were not correlated with T or FSH.…”
supporting
confidence: 91%
“…For example, we did not control for polychlorinated biphenyls (PCBs) or phthalate exposures, which have both been identified to be inversely associated with testosterone in males (Goncharov et al, 2009;Meeker and Ferguson, 2014;Specht et al, 2014). These associations tend to be opposite in direction to the positive association between lead and testosterone this analysis identified.…”
Section: Discussionmentioning
confidence: 98%
“…PCBs also alter sex hormone function, with many congeners and hydroxylated metabolites having estrogenic activity (59). Elevated PCB exposure results in earlier puberty in girls (60) and a reduction in testosterone levels in men and boys (61,62). PCBs suppress the immune system, leading to increased respiratory infections in children (63,64) and elevations in cases of asthma (64,65).…”
Section: Discussionmentioning
confidence: 99%